Penerapan Snort Sebagai Sistem Keamanan Jaringan - Jusep Ferlyzon; Indra Kanedi; Reno Supardi (UNIVED Press, 2025)
SMA Negeri 5 South Bengkulu is one of the State Senior High Schools in South Bengkulu Regency, Bengkulu Province. The school already has internet access and a computer network in the Lab that can be accessed by teachers, students, and staff within the school. However, access to the network does not yet have a security system that can prevent several threats from attacking the network. The purpose of this research is to implement snort on computer networks at SMA Negeri 5 South Bengkulu. Securing the computer network at SMA Negeri 5 South Bengkulu to avoid unwanted things by implementing Snort in it which will detect if there is a threat of attacks. Snort will be tasked with detecting attacks that occur if a client attacks the server in the form of pinging of death or DDos attacks. Based on the test results that have been carried out, the application of snort can help schools in knowing security system information on computer networks at school, as well as securing computer networks at school.